Market liberalization in the European natural gas market : the importance of capacity constraints and efficiency differences - Steven Brakman; Charles van Marrewijk; Arjen van Witteloostuijn (Center for Economic Studies and ifo Institute (CESifo), 2009)
In the European Union, energy markets are increasingly being liberalized. A case in point is the European natural gas industry. The general expectation is that more competition will lead to lower prices and higher volumes, and hence higher welfare. This paper indicates that this might not happen for at least two reasons. First, energy markets, including the market for natural gas, are characterized by imperfect competition and increasing costs to develop new energy sources. As a result, new entrants in the market are less efficient than incumbent firms. Second, energy markets, again including the market for natural gas, are associated with capacity constraints. Prices are determined in residual markets where the least efficient firms are active. This is likely to lead to price increases, rather than decreases.
Keywords: D40; L10; L50; 330; Gaswirtschaft; Deregulierung; Unvollkommener Wettbewerb; Wirtschaftliche Effizienz; Produktionskapazität; Bottleneck; Preis; EU-Staaten